Development of pole-like tree spiral climbing robot - Mustapa, M.A. (Pleiades Publishing, 2018)
This paper presents a tree climbing robot which moves spirally around a pole-like tree of having a circumference of around 40Â cm. The aim of this work is to ease the work of inducing Aquilaria trees. The designed robot is able to climb with overall weight of the robot can carry is limit to 10Â kg. The robot utilizes the wheel mechanism as the locomotion of the robot. Driving module uses two DC motors, and the robot also uses a set of springs and castor balls as a supporting mechanism. To achieve the robot spiral climbing morphology, two DC motors are used as the steering module. At the current stage of development, the angle of climbing is controlled manually by DIP-switches. The advantages of this robot are low cost, uses simple mechanism, easy to control and fabricate. The robot has been built and successfully tested on a tree trunk and PVC tube. Experiment has been carried out to evaluate the speed performances of the prototype. Results indicate that the robot is able to climb in spiral motion with largest error recorded at 13.9. Â© 2018, Springer Nature Singapore Pte Ltd.